EFFECT OF POLYAMINES ON POSTHARVEST QUALITY AND VASELIFE OF ROSE VAR. SAMURAI - SUMATHI TATTE,; ALKA SINGH,; T. R. AHLAWAT, (The Bioscan, 2015)
Investigation was conducted to study the influence of different polyamines in spray form on post harvest life of rose var. Samurai. Polyamines viz. spermine, spermidine and putrescine at three different concentrations 10, 20, 50 ppm and water as control were used as postharvest spray treatments. Among all the treatments, cut roses var. Samurai sprayed with spermine @ 10ppm, followed by spermidine @10 ppm showed maximum water uptake (95.82 ml) and higher fresh weight retention (27.55, 26.03 and 18.97 g) as recorded respectively on 3rd, 5th and 7th day of vase life. Further, maximum total soluble sugars (65.32, 62.83 and 59.42μg/ml) and minimum electrolyte leakage (33.01, 63.09 and 75.70 %) in the petal tissue were observed with same treatments. Roses treated with 10 ppm spermine showed slower bud opening from day 1 to day 7) and enhanced vase life (8.03 days), followed by 10 ppm spermidine (7.76 days) as compared to control (4.24 days). Thus, the treatment 10 ppm of spermine improved flower quality and extended vase life by three days in rose cut flowers.